Association of long term antibiotic use and diagnosis of chronic disease - Wachtel, S; Hoang, U; Sherlock, J; McGee, C; Byford, R; De Lusignan, S (Mashhad University of Medical Sciences, 2018)
Background: There has recently been increasing interest in the role of the human microbiome in disease. Antibiotic use is known to disrupt the intestinal microbial environment and cause acute disease, for example pseudomembranous colitis. This study aimed to investigate the hypothesis that long-term antibiotic use is associated with the development of chronic diseases, i.e., Asthma, Rheumatoid Arthritis, Inflammatory Bowel Disease, Colorectal Cancer, and Dementia. Methods: The study is a retrospective observational study using ontologically defined cases recorded by primary care physicians covering the period 2004 to 2015 combined with prescribing data. The study is primary care based, utilizing records held by the Royal College of General Practitioners Research and Surveillance Centre (RCGP RSC) database, representative of all English General Practices, over the period 2004 to 2015 inclusive. All patients registered with practices subscribing to the RCGP RSC database, with 10 years of prescribing history and other full demographic information required for the study recorded, numbering 644,273 were utilized. All records were analyzed for demographic data, diagnoses of study, known risk factors, and prescribing history of antibiotics. Exclusion criteria included incomplete data for known risk factors or demographics. The main outcome measures are the odds ratios (OR) of being diagnosed with one of the diseases of the study per antibiotic prescription issued over the preceding decade before diagnosis, adjusted for demographics and known risk factors. Results: The OR (2.5% CI, 97.5% CI) of being diagnosed with Asthma was 1.004 (1.002, 1.006), Rheumatoid Arthritis 1.006 (1.003, 1.008), Inflammatory Bowel Disease 1.007 (1.006, 1.008), Colorectal Cancer 1.001 (0.999, 1.002), and Dementia 1.001 (0.998, 1.001). Conclusions: The long-term use of antibiotics is associated with a statistically significant dose related increase in the odds of being diagnosed with asthma, rheumatoid arthritis and inflammatory bowel disease, but not all forms of dementia or colorectal cancer. Potential mechanisms include chronic disruption of the microbiome. This finding has implications for practitioners who prescribe antibiotics, the pharmaceutical industry, policy makers, and researchers involved in studying chronic disease mechanisms.